REORIENTASI PENDIDIKAN PESANTREN (TELAAH ATAS TUJUAN PENDIDIKAN ISLAM DI PONDOK PESANTREN AL-ISLAM JORESAN MLARAK PONOROGO) - Arkam, Rohmad (Universitas Islam Balitar, 2018)
This research is aiming at examining the reorientation of Islamic boarding schools for the purpose of Islamic education in the Al-Islam Joresan Mlarak Ponorogo Islamic boarding school. This study included as a descriptive research, a case study was in the Al-Islam Joresan Mlarak Ponorogo boarding school. In collecting data, the writer used methods of interview, observation, and documentation. The techniques of analyzing data are reduction data, displaying data, and drawing conclusion or verification. Based on the result of the research, it was found that (1) background of reorientation of Islamic education in Al Islam Islamic boarding school conveys that it is indifferent toward the challenges of social change, participating themselves in social changes and playing role as an agent of social change (2 ) the aim of development of Islamic education at Islamic boarding school Al Islam Josaren Mlarak Ponorogo is in accordance with the Neo-Modernism model, it is a method trying to understand the basic thoughts and values contained in the Al Qur ’an and As Sunnah by implicating and considering the treasures of classical intellectual Muslims. (3)the design of reorientation in Al Islam Islamic boarding school is a curriculum development, evaluation and institutionaldevelopment.